Accompanying evalution of funded projects in palliative medicine of the German Cancer Aid Begleitevaluation des Förderschwerpunkts Palliativmedizin der Deutschen Krebshilfe - Ostgathe, Christoph; Lindena, G.; Heussen, N.; Knübben, K.; Elsner, F.; Radbruch, L. (Schmerz, 2011)
The German Cancer Aid funded 12 regional projects which developed different models of palliative home care. The realization of the projects were concurrently monitored and evaluated. The funded projects were asked to document all patients who were cared for beginning in January 2009 using HOPE (Hospice and palliative survey), MIDOS (Minimal documentation system for palliative patients) and the Barthel index. Documentation was mandatory at the beginning and the end of care as well as when patients changed settings, for example when patients were transferred from a palliative care unit to a palliative home care service. Additionally the projects were visited by an independent observer. Overall the 12 projects documented 2,663 patients. Analysis revealed differences between the projects mainly concerning target groups and interventions. The results of this evaluation can support the discussion about the development of palliative home care in Germany with particular focus on possible interrelations between structures, target groups and possible outcomes of care. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2025-10-27
Keywords: Documentation; Evaluation; Outpatients; Palliative care; Quality assurance